Fate of MS2 proteins synthesized in Escherichia coli exposed to amino acid analogues. - Prouty, W F (1975)
Incorporation of an analoque into MS2 coded proteins prevents the maturation of phages. In addition, there is an alteration in the relative amount of coat protein to replicase protein synthesized, which supports the hypothesis that normal coat protein serves a physiological role as a translation repressor. Further, abnormal proteins, synthesized from the phage genome, are degraded, presumably by a host catabolic system, more rapidly than the normal gene products.